FDA Approval Summary: Pembrolizumab for Treatment of Metastatic Non‐Small Cell Lung Cancer: First‐Line Therapy and Beyond - Pai‐Scherf, Lee; Blumenthal, Gideon M.; Li, Hongshan; Subramaniam, Sriram; Mishra‐Kalyani, Pallavi S.; He, Kun; Zhao, Hong; Yu, Jingyu; Paciga, Mark; Goldberg, Kirsten B.; McKee, Amy E.; Keegan, Patricia; et al. (The oncologist (Dayton, Ohio), 2017)
On October 24, 2016, the U.S. Food and Drug Administration (FDA) approved pembrolizumab (Keytruda; Merck & Co., Inc., https://www.merck.com) for treatment of patients with metastatic non‐small cell lung cancer (mNSCLC) whose tumors express programmed death‐ligand 1 (PD‐L1) as determined by an FDA‐approved test, as follows: (a) first‐line treatment of patients with mNSCLC whose tumors have high PD‐L1 expression (tumor proportion score [TPS] ≥50%), with no epidermal growth factor receptor (EGFR) or anaplastic lymphoma kinase (ALK) genomic tumor aberrations, and (b) treatment of patients with mNSCLC whose tumors express PD‐L1 (TPS ≥1%), with disease progression on or after platinum‐containing chemotherapy. Patients with EGFR or ALK genomic tumor aberrations should have disease progression on FDA‐approved therapy for these aberrations prior to receiving pembrolizumab. Approval was based on two randomized, open‐label, active‐controlled trials demonstrating statistically significant improvements in progression‐free survival (PFS) and overall survival (OS) for patients randomized to pembrolizumab compared with chemotherapy. In KEYNOTE−024, patients with previously untreated mNSCLC who received pembrolizumab (200 mg intravenously [IV] every 3 weeks) had a statistically significant improvement in OS (hazard ratio [HR] 0.60; 95% confidence interval [CI]: 0.41–0.89; p = .005), and significant improvement in PFS (HR 0.50; 95% CI: 0.37–0.68; p < .001). In KEYNOTE‐010, patients with disease progression on or after platinum‐containing chemotherapy received pembrolizumab IV 2 mg/kg, 10 mg/kg, or docetaxel 75 mg/m2 every 3 weeks. The HR and p value for OS was 0.71 (95% CI: 0.58–0.88), p < .001 comparing pembrolizumab 2 mg/kg with chemotherapy and the HR and p value for OS was 0.61 (95% CI: 0.49–0.75), p < .001 comparing pembrolizumab 10 mg/kg with chemotherapy. Implications for Practice This is the first U.S. Food and Drug Administration approval of a checkpoint inhibitor for first‐line treatment of lung cancer. This approval expands the pembrolizumab indication in second‐line treatment of lung cancer to include all patients with programmed death‐ligand 1‐expressing non‐small cell lung cancer. This FDA approval summary provides an update on approval of pembrolizumab for treatment of patients with metastatic non‐small cell lung cancer whose tumors express PD‐L1 as determined by an FDA‐approved test. The results of KEYNOTE‐010 and KEYNOTE‐024 trials are presented.